1980
DOI: 10.1063/1.439114
|View full text |Cite
|
Sign up to set email alerts
|

Computational kinetics and sensitivity analysis of hydrogen–oxygen combustion

Abstract: Kinetic modeling calculations on the H2–O2 system have been carried out with an extensive reaction set to probe the vicinity of the three explosion limits. Sensitivity analysis is used throughout this investigation to study system behavior, in particular, to elucidate mechanistic details. The concentrations and sensitivity profiles are discussed in light of the appropriate experimental results and existing theories of hydrogen combustion. The results indicate the present model to be useful over a wide pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…Rare recent mechanisms, e.g., [36], include reactions of ozone even though Dougherty and Rabitz [49] demonstrated that pertinent reactions are not important over all conditions of hydrogen oxidation covering three explosion limits. Likewise vibrationally or electronically excited species are not considered in the contemporary combustion models, although some disputable arguments were put forward in the literature, e.g., [50].…”
Section: Species Thermodynamic and Transport Parametersmentioning
confidence: 98%
“…Rare recent mechanisms, e.g., [36], include reactions of ozone even though Dougherty and Rabitz [49] demonstrated that pertinent reactions are not important over all conditions of hydrogen oxidation covering three explosion limits. Likewise vibrationally or electronically excited species are not considered in the contemporary combustion models, although some disputable arguments were put forward in the literature, e.g., [50].…”
Section: Species Thermodynamic and Transport Parametersmentioning
confidence: 98%
“…Contemporary detailed kinetic schemes silently ignore reactions of ozone and of excited species. For instance, reactions of ozone are not included since Dougherty and Rabitz [174] demonstrated that pertinent chemistry is not important over all conditions of hydrogen oxidation covering three explosion limits. Although possible channels of excited atomic oxygen formation were considered [54], their role remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…These turning points separate the first branch (lower pressures) from the second branch (higher pressures). The two ignition branches are reminiscent of the first and second explosion limits (Dougherty and Rabitz, 1980;Galand, 1981;Gray et al, 1984;Chin nick et al, 1986;Griffiths and Scott, 1987;Baulch .et aI., 1988;Gray and Scott, 1990;Johnson et al; (Gray and Scott, 1990). …”
Section: <1>=05mentioning
confidence: 96%